Technology Acceptance Model (TAM) and Perceived Risk in Online Purchase Decisions for Traditional Foods, Indonesia - Avivah Rahmaningtyas; Anisa Kusumawardani (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Digital platforms offer consumers a convenient alternative for purchasing traditional foods from various regions. This study’s objective is to investigate the influence of the Technology Acceptance Model (TAM) and Perceived Risk (PR) on buying decisions for Indonesian traditional food. Data were collected through a questionnaire distributed to 150 respondents who had previously purchased traditional foods through online stores. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to examine the data. The study’s results show that Perceived Usefulness (PU) and Perceived Ease of Use (PEU) have a positive and significant effect on Purchase Decision (PD), as indicated by T-statistic values greater than 1.960 at the 5% significance level, namely 3.284 for the PU variable and 3.386 for the PEU variable. Meanwhile, PR shows no statistically significant influence, as indicated by a T-statistic of 0.804, which falls short of the significance threshold of 1.960. This study contributes by focusing specifically on Indonesian traditional food products, offering novelty in online food-purchase research, and by integrating TAM and PR, which sets it apart from prior studies. In practice, the findings suggest that to provide a better shopping experience and encourage purchasing decisions, businesses should improve the usefulness and ease of use of their online platforms. A key limitation is the exclusive use of TAM without incorporating consumer behavior theories. Thus, future research is recommended to combine TAM with theories such as TPB and TRA to analyze consumer decision-making.